Determinants of Tax Compliance in Surabaya : A Study of Cognition, Volition, and Tax Avoidance - Rodhiyah Rodhiyah (International Journal of Economics and Management Research, 2024)
This research addresses the growing concerns of declining tax realization and widespread tax avoidance, which have resulted in significant revenue losses for the government. The study emphasizes the necessity of improving tax policy implementation and enhancing societal awareness to address these challenges and optimize taxpayer compliance. The primary objective of this research was to analyze the impact of socialization, information technology, attitudes, knowledge, and tax-paying abilities on taxpayer compliance, with awareness and volition acting as intervening variables and tax avoidance as a moderating factor. The focus of this study is on individual taxpayers in Surabaya. The study employed an explanatory design, with a population consisting of individual taxpayers registered with the KPP East Java Region I, totaling 3,042,548 people as of 2020. A sample of 400 respondents was selected using the Slovin formula to represent this population. Data analysis was carried out using Smart PLS. The findings revealed that socialization had a positive effect on taxpayer awareness but a negative impact on volition and taxpayer compliance. Information technology had mixed effects, showing an insignificant influence on certain factors. Attitudes had a significant impact on awareness and volition, although its influence on compliance was not significant. Knowledge strongly influenced awareness, volition, and taxpayer compliance, while the ability to pay taxes positively affected awareness, volition, and compliance. Additionally, the study found mixed influences of awareness and volition on taxpayer compliance when moderated by tax avoidance. These findings provide valuable insights into the factors affecting taxpayer behavior and compliance, confirming or contradicting previous research on this topic. The study underscores the importance of targeted tax education and awareness programs to foster greater taxpayer compliance, thereby contributing to enhanced regional and state revenues.